CURVILINEAR CO-ORDINATES AND EXPRESSION OF MOTION EQUATIONS FROM VECTOR FORM TO CYLINDRICAL CO-ORDINATES - MASIBAYI, ANDREW; CYPRIAN, O. S.; OKELO, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we consider at the equations of motion in vector form and convert them tocylindrical coordinates. We also consider the continuity and momentum properties of theseequations.